2021
DOI: 10.1155/2021/5521493
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Logistic Regression Model for a Dataset to Predict Diabetic Foot Ulcer in Diabetic Patients: High-Density Lipoprotein (HDL) Cholesterol Was the Negative Predictor

Abstract: Objectives. Although the risk factors for diabetic neuropathy and diabetic foot ulcer have been detected, there was no practical modeling for their prediction. We aimed to design a logistic regression model on an Iranian dataset to predict the probability of experiencing diabetic foot ulcers up to a considered age in diabetic patients. Methods. The present study was a statistical modeling on a previously published dataset. The covariates were sex, age, body mass index (BMI), fasting blood sugar (FBS), hemoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Likewise, DD is associated with microvascular complications such as peripheral neuropathy related to the effect of fatty acids on mitochondrial traffic [ 63 ]. The deposition of these substances associated with lipid metabolism causes oxidative stress followed by increased expression of pro-inflammatory cytokines and neuronal apoptosis [ 64 ]. This neuropathic compromise is even associated with the initial lipid profile of the patient with a recent diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, DD is associated with microvascular complications such as peripheral neuropathy related to the effect of fatty acids on mitochondrial traffic [ 63 ]. The deposition of these substances associated with lipid metabolism causes oxidative stress followed by increased expression of pro-inflammatory cytokines and neuronal apoptosis [ 64 ]. This neuropathic compromise is even associated with the initial lipid profile of the patient with a recent diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…e deposition of these substances associated with lipid metabolism causes oxidative stress followed by increased expression of pro-in ammatory cytokines and neuronal apoptosis [64].…”
Section: Discussionmentioning
confidence: 99%
“…Lower HDL‐C levels are associated with amputation in patients with DFU, and this association is independent of other risk factors. Ahmadi 18 et al have come to similar results, low levels of HDL‐C are associated with LEA causes in patients with DFU, HDL‐C can be used as a predictor of LEA in patients with DFU, and hdl‐C levels are strongly recommended to be maintained above 50 mg/dL. Therefore, this study suggests that keeping HDL‐C in the normal range may reduce the risk of lower extremity amputation in patients with DFU.A study by Guo et al in Hunan Province, China, concluded that reductions in triglyceride and HDL‐C levels were significantly associated with higher amputation rates, but that only a decrease in triglyceride levels was an independent predictor of lower limb amputation (OR 0.255).…”
Section: Discussionmentioning
confidence: 99%
“…32 It is also the only negative predictor of risk for diabetic foot ulcers. 33 In addition, higher levels of sphingolipids DSLs, associated with diabetic neuropathy, were found in patients with type 2 diabetes mellitus (T2DM), highlighting the intricate connection between lipid metabolism and diabetic neuropathy. 34 Insulin resistance (IR) plays a crucial role in the pathogenesis of diabetic neuropathy, and IR has a more significant role in T2DM neuropathy.…”
Section: Pathog Ene S Is Of D Iab E Ti C Neuropathymentioning
confidence: 99%
“…Studies also show that high‐density lipoprotein cholesterol is associated with the later development of diabetic neuropathy 32 . It is also the only negative predictor of risk for diabetic foot ulcers 33 . In addition, higher levels of sphingolipids DSLs, associated with diabetic neuropathy, were found in patients with type 2 diabetes mellitus (T2DM), highlighting the intricate connection between lipid metabolism and diabetic neuropathy 34 …”
Section: Pathogenesis Of Diabetic Neuropathymentioning
confidence: 99%